Effect of Information Sharing on Organizational Commitment in Insurance Companies in Uasin Gishu County, Kenya - Mandago, Dr. Rael; Kipcumba , Johnstone Tarus (European Journal of Human Resource, 2024)
Purpose: To assess the effect of information sharing on organizational commitment in insurance companies in Uasin Gishu County, Kenya Materials and Methods: Quantitative techniques were used for both data collection and analysis. The target population was 754 respondents who were drawn from the insurance companies in Uasin Gishu County. the sample size was 260 determined using Krejcie and Morgan table 1970. After the sample size of 260 respondents. Simple random sampling was used to select the respondents to participate in the research study, but after it had been determined how many from each of the insurance companies participated. Under Inferential Statistics, Multiple Regressions was used to determine the effect of a set of independent variable (high involvement work systems) on dependent variable (organizational commitment), Co-efficient of Correlation using the Statistical Package for Social Sciences (SPSS) version 25.0 package Findings: Regression between information sharing and organizational commitment were was positive and significant ((b=0.322,p=0.000). Based on the t-test results the null hypothesis was rejected. Thus, there is a significant effect of information sharing on Organizational Commitment in insurance companies in Uasin Gishu County, Kenya. Implications to Theory, Practice and Policy: Information sharing ensure that employees receive for their job responsibilities and relevant extra role duties for purposes of their commitment to the organization. In this regard the insurance companies should ensure their information sharing criteria meets the threshold of information quality dimensions, such as timeliness and correctness accuracy, completeness, consistency, timeliness, validity, and uniqueness so as to engender positive employee behaviors as organizational commitment.